An integrated and coordinated approach to preventing recurrent coronary heart disease events in Australia - Briffa, Tom; Kinsman, L.; Maiorana, Andrew; Zecchin, R.; Redfern, J.; Davidson, Patricia; Paull, G.; Nagle, A.; Denniss, A (Australasian Medical Publishing Company (AMPCo), 2009)
Implementing existing knowledge about cardiacrehabilitation (CR) and heart failure management couldmarkedly reduce mortality after acute coronary syndromesand revascularisation therapy. Contemporary CR and secondary prevention programs arecost-effective, safe and beneficial for patients of all ages,leading to improved survival, fewer revascularisationprocedures and reduced rehospitalisation. Despite the proven benefits attributed to these secondary prevention interventions, they are not well attended bypatients. Modern programs must be flexible, culturally safe,multifaceted and integrated with the patients primary healthcare provider to achieve optimal and sustainable benefits for most patients.